The Role of PKN Teachers in Integrating PKN Material Based on Local Wisdom at Junior High School 1 Maumere - Yuliana Imelda Densius; Gisela Nuwa; M. Ihsan Wahab (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
The world of education is the most effective way to instill basic values, especially those born from local customs to be used as material in the learning process. For example, the integration of civics material based on local wisdom. Through an understanding of local wisdom, students can love, preserve, and introduce regional culture to the next generation so that local wisdom is not lost along with the times, and can instill noble values such as tolerance, mutual cooperation, and social concern which are very important for the formation of student character. The purpose of this study is to describe the role of civics teachers in integrating civics material based on local wisdom at SMP Negeri 1 Maumere and identify the challenges faced by civics teachers in integrating civics material based on local wisdom. This study uses a descriptive qualitative method, the main data sources are the Principal, and Civics subject teachers. Secondary data sources are lesson implementation plans (RPP), teaching materials, and other sources from articles and books. Data collection techniques used are interviews, observations, and documentation. Data analysis by collecting data, reducing data, presenting data, and finally drawing conclusions. The role of teachers in integrating local wisdom-based civics material at SMP Negeri 1 Maumere is to use various teaching methods, various teaching media, plan effective learning, build good relationships with students, understand individual needs of students, practice local wisdom values in everyday life and evaluate themselves. However, in this role there are challenges faced by civics subject teachers that can come from within themselves, other people and the surrounding environment.